Boonesborough unearthed : frontier archaeology at a Revolutionary fort - O'Malley, Nancy (The University Press of Kentucky, 2019)
"Throughout the Revolutionary War, Fort Boonesborough was one of the most important and defensively crucial sites on the western frontier. It served not only as a garrison against the British but also as a sanctuary, land office, and a potential seat of government. Originally meant to be the capital of a new American colony, Fort Boonesborough was thrust into a defensive role by the onset of the Revolutionary War. Post-Revolutionary attempts to develop a town failed and the site was abandoned. Yet Fort Boonesborough lived on in local memory. Boonesborough Unearthed: Frontier Archaeology at a Revolutionary Fort is the result of more than 30 years of research by archaeologist Nancy O'Malley. This groundbreaking book presents new information and fresh insights about Fort Boonesborough and life in frontier Kentucky. O'Malley examines the story of this historical landmark from its founding during a time of war into the nineteenth century. O'Malley also delves into the lives of the settlers who lived there, and explores the dashed hopes of the Transylvania Company to form a fourteenth colony. This insightful and informative work is a fascinating exploration into Kentucky's frontier past"--